PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BIRO PEMELIHARAAN BANGUNAN DAN INSTALASI SEKRETARIAT JENDERAL DPR-RI - Lis Andayani (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: The research was conducted to identify and analyze the effect of Motivation and Work Discipline to Employee Performance of Biro Pemeliharaan Bangunan dan Instalasi Sekretariat Jenderal DPR-RI. Data obtained by distributing questionnaires to 55 employees who were respondents. Research method used explanatory research,testing using multiple regression analysis and correlation analysis. The results of the simultaneous analysis showed that Motivation and Work Discipline have significant effect on employee performance. The magnitude of the correlation is positive and strong, the Disciplined Work much stronger influence than Motivation. Testing either partially Motivation and Work Discipline have significant effect on employee performance. Thereby increasing the motivation and Work discipline, EmployeePerformance will increase or better. Advice can be given to the organization and employees can increase motivation by inviting motivator, rewarding and publicity, employees also need to improve the quality of self and develop potential, can use office equipment. To Discipline of work by the way, do not leave or delegate work to others, using hours just to do the work, does not violate the hour came and curfew hours.Keywords: motivation, work discipline, employee performance.